Pharmacological activities and mechanisms of action of hypophyllanthin: A review - Wan Saidin, Wan Azmira; Jantan, Ibrahim; Abdul Wahab, Siti Mariam; Jalil, Juriyati; Mohd Said, Mazlina; Yusoff, Syaratul Dalina; Husain, Khairana (Frontiers in Pharmacology, 2023)
Hypophyllanthin is a major lignan present in various Phyllanthus species and has been used as one of the bioactive chemical markers for quality control purposes as it contributes to their diverse pharmacological activities. The objective of this study is to compile up-to-date data on the pharmacological actions and mechanisms of hypophyllanthin. This review also includes the extracts of Phyllanthus species whose pharmacological actions have been partially attributed to hypophyllanthin. The scientific findings on the compound are critically analyzed and its potential as a lead molecule for discovery of drug candidates for development of therapeutics to treat diverse diseases is highlighted. Data collection was mainly through the exploration of Ovid-MEDLINE, Scopus, Science Direct, and Elsevier databases. Studies conducted in vitro and in vivo showed that hypophyllanthin had potent immunomodulating properties as well as a variety of other pharmacological properties, including anti-inflammatory, hepatoprotective, anti-tumor, anti-allergic, anti-hypertensive, and phytoestrogenic properties. Several mechanisms of action on the effects of hypophyllanthin on the immune system, in cancer and other disease states were presented to provide some insights on its pharmacological effects. Before being submitted to clinical investigations, additional animal studies utilising different animal models are necessary to analyse its bioavailability, pharmacokinetics, and pharmacodynamic properties, as well as its toxicity, to determine its efficacy and safety. Understanding its potential as a lead molecule for the discovery of therapeutic candidates, particularly for the development of therapies for inflammatory and immune-related disorders, requires an understanding of its pharmacological activities and mechanisms of action. An insight on its pharmacological activities and mechanisms of action will provide understanding of its potential as a lead compound for discovery of drug candidate especially for development of therapies for inflammatory and immune related diseases.